A CONSTRUÇÃO DA IDENTIDADE DOCENTE DE LICENCIADOS EM FÍSICA E MATEMÁTICA: RELATOS SOBRE O PROCESSO FORMATIVO - Ferreira, Álex de Carvalho (2020)
In this article we present a dialogue about the formative process in undergraduate courses in Physics and Mathematics through experience reports, focusing on the training of teachers in these areas, as well as the process of identity construction in the course of initial formation. Based on studies on teaching identity (DUBAR, 2005; GOMES, 2008; PIMENTA; LIMA, 2004) and considering the importance of how the process of building this teaching identity occurs, we discuss the paths and experiences that contributed to this construction in order to propose a discussion that can contribute, by reflecting on pedagogical actions and teacher identity, complementing existing studies for a better understanding in the process of teacher training, especially the teaching of Physics and Mathematics.